Pancreas-Brain Crosstalk - Lkhagvasuren, Battuvshin; Mee-inta, Onanong; Zhao, Zi-Wei; Hiramoto, Tetsuya; Boldbaatar, Damdindorj; Kuo, Yu-Min (Frontiers in Neuroanatomy, 2021)
The neural regulation of glucose homeostasis in normal and challenged conditions involves the modulation of pancreatic islet-cell function. Here, we review the neuroanatomical and humoral basis of the cross-talk between the endocrine pancreas and autonomic and sensory neurons, including the extrapancreatic efferent and afferent pathways, intrapancreatic nervous division (neuro-insular complex), the enteropancreatic plexus, and the humoral crosstalk between the circumventricular organs and the pancreas. Identifying the neurocircuitry and neurochemistry of the neuro-insular network would provide clues to neuromodulation-based approaches for the prevention and treatment of diabetes and obesity.